Introducing standardized “readbacks” to improve patient safety in surgery: a prospective survey in 92 providers at a public safety-net hospital - Prabhakar, Hari (BioMed Central, 2012)
BACKGROUND: Communication breakdowns represent the main root cause of preventable complications which lead to harm to surgical patients. Standardized readbacks have been successfully implemented as a main pillar of professional aviation safety for decades, to ensure a safe closed-loop communication between air traffic control and individual pilots. The present study was designed to determine the perception of staff in perioperative services regarding the role of standardized readbacks for improving patient safety in surgery at a single public safety-net hospital and level 1 trauma center. METHODS: A 12-item questionnaire was sent to 180 providers in perioperative services at Denver Health Medical Center. The survey was designed to determine the individual participants’ perception of (1) appropriateness of current readback processes; (2) willingness to attend a future training module on this topic; (3) specific scenarios in which readbacks may be effective; and (4) perceived major barriers to the implementation of standardized readbacks. Survey results were compared between departments (surgery versus anesthesia) and between specific staff roles (attending or midlevel provider, resident physician, nursing staff), using non-parametric tests. RESULTS: The response rate to the survey was 50.1 % (n = 92). Respondents overwhelmingly recognized the role of readbacks in reducing communication errors and improving patient safety. There was a strong agreement among respondents to support participation in a readbacks training program. There was no difference in the responses between the surgery and anesthesia departments. There was a statistically significant difference in the healthcare providers willingness to attend a short training module on readbacks (p < 0.001). Resident physicians were less likely to endorse the importance of readbacks in reducing communication errors (p = 0.01) and less willing to attend a short training module on readbacks (p < 0.001), as compared to staff providers and nursing staff. The main challenge for respondents, which emanated from their responses, appeared to relate to determining the ideal scenarios in which readbacks may be most appropriately used. Overall, respondents strongly felt that readbacks had an important role in patient handoffs, patient orders regarding critical results, counting and verifying surgical instruments, and delegating multiple perioperative tasks. CONCLUSION: The majority of all respondents appear to perceive standardized readbacks as an effective tool for reducing and/or preventing adverse events in the care of surgical patients, derived from a breakdown in communication among perioperative caregivers. Further work needs to be done to define the exact clinical scenarios in which readbacks may be most efficiently implemented, including the definition of a uniform set of scripted quotes and phrases, which should likely be standardized in concert with the aviation safety model.